Evaluation of Therapeutic Methods used for the Treatment of Diabetic Foot Syndrome - Hasan, Naser (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: Recent studies have shown a rampant increase in the number of patients with diabetes around the world. This constitutes an economic burden on the resources of states and hence has prompted many international organizations to devise awareness and educational programs about the dangers of this the disease and ways to deal with it. There are serious complications to diabetes which may include; high blood pressure, heart and kidney diseases, eye problems, neuropathy, and diabetic foot. The most feared development of this disease is the diabetic foot as it may lead to amputation. This study examines the prevalence of diabetes and complementary alternative medicine in the treatment of this disease and the attitudes toward managing diabetic foot in Makkah and Taif area in Saudi Arabia. Methods: Questionnaires were distributed in the Western region of Saudi Arabia.The sample size was 750. Responses were collected and proper descriptive statistical analysis was applied. Results: An alarming 34% of respondents have diabetes, 74% of surveyed population has diabetes within family members, and 40% of respondents have had a form of foot problem with the highest incident of leg pain and numbness. The majority of examined population has chosen traditional medical intervention rather than herbal medicine in dealing with foot problems. Conclusions: The culture of interfamily marriages has to be overlooked to curb rampant increase of diabetes incidents among family members. There is lack of statistical data related to the incident rate of lower-extremity amputations LEA among patients with diabetes in Saudi Arabia. Moreover, the role of diabetic centers has to be invigorated in spreading knowledge with regards to diabetes, and in devising proper follow-up procedures to patients with diabetes after referral to other departments in hospitals